Development of Teaching Materials Based on Predict-Observe-Explain (POE) Model by Integrating PhET Virtual Laboratory on Temperature and Heat Material - Indah Permata Sari; Laili Komariyah; Atin Nuryadin; Riskan Qadar (Jurnal Materi dan Pembelajaran Fisika, 2025)
Physics subjects, particularly the material on Temperature and heat, are often considered difficult due to the abstract nature of the concepts, which can lead to student misconceptions. This challenge is compounded by findings that the learning models and methods used in the field were still conventional and that many schools experience limitations in laboratory equipment for hands-on practicum. To address this gap and promote active student involvement, this study aims to develop teaching materials based on the Predict-Observe-Explain (POE) model integrated with the PhET virtual simulation on temperature and heat material. The research utilized the Research and Development (R&D) method using the 4D model (Define, Design, Develop, and Disseminate), with the study limited to the Develop stage. The research instruments included expert validation sheets and a student response questionnaire. The validation results from material and media experts obtained a high score of 89%, which is classified into the “Very Valid” category. Furthermore, the limited trials showed a positive average student response of 77%, classified in the “Good” category. The successful integration of the POE model with the PhET simulation proved effective in helping students understand the concepts of temperature and heat and increasing their active involvement in the learning process. In conclusion, the developed teaching material is highly suitable for use in the learning process at the high school level and serves as a significant practical contribution by providing an alternative interactive learning media that supports the Merdeka Curriculum.